Non-Fouling Biodegradable Poly(ϵ-caprolactone) Nanofibers for Tissue Engineering - Kostina, Nina Yu; Pop-Georgievski, Ognen; Bachmann, Michael; Neykova, Neda; Bruns, Michael; Michálek, Jiří; Bastmeyer, Martin; Rodriguez-Emmenegger, Cesar (Macromolecular bioscience, 2016)
Poly(ϵ-caprolactone) (PCL) nanofibers are very attractive materials for tissue engineering (TE) due to their degradability and structural similarity to the extracellular matrix (ECM). However, upon exposure to biological media, their surface is rapidly fouled by proteins and cells, which may lead to inflammation and foreign body reaction. In this study, an approach for the modification of PCL nanofibers to prevent protein fouling from biological fluids and subsequent cell adhesion is introduced. A biomimetic polydopamine (PDA) layer was deposited on the surface of the PCL nanofibers and four types of antifouling polymer brushes were grown by surface-initiated atom transfer radical polymerization (SI-ATRP) from initiator moieties covalently attached to the PDA layer. Cell adhesion was assessed with mouse embryonic fibroblasts (MEFs). MEFs rapidly adhered and formed cell-matrix adhesions (CMAs) with PCL and PCL-PDA nanofibers. Importantly, the nanofibers modified with antifouling polymer brushes were able to suppress non-specific protein adsorption and thereby cell adhesion.
Keywords: testování materiálů; Tissue Engineering; Protein Binding; Cell Adhesion; Cells, Cultured; Nanofibers; Mice; zvířata; tkáňové inženýrství; bioznečištění; polyestery; Biofouling; vazba proteinů; kultivované buňky; myši; Animals; buněčná adheze; Materials Testing; Polyesters; nanovlákna